2006
DOI: 10.1177/112067210601600412
|View full text |Cite
|
Sign up to set email alerts
|

Pars Plana Vitrectomy and Removal of the Internal Limiting Membrane in Diabetic Macular Edema Unresponsive to Grid Laser Photocoagulation

Abstract: PPV with ILM removal appears to be an effective procedure for reducing diabetic macular edema unresponsive to grid laser photocoagulation. A further study with a large number of patients is required to assess the effectiveness and safety of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 31 publications
0
23
0
1
Order By: Relevance
“…Several studies have reported favorable results by reducing or resolving DME and improving VA following PPV combined with ILM removal [3,4,5,6,7,8,9,10,11,12]. However, anatomical outcome may not always be correlated with functional results after PPV with ILM removal.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have reported favorable results by reducing or resolving DME and improving VA following PPV combined with ILM removal [3,4,5,6,7,8,9,10,11,12]. However, anatomical outcome may not always be correlated with functional results after PPV with ILM removal.…”
Section: Discussionmentioning
confidence: 97%
“…Earlier studies involving OCT mostly focused on macular edema and a correlation was found between visual acuity (VA) and reduction in central macular thickness [7,8,9,10,11,12]. However, some eyes with DME have a poor visual outcome despite resolution of macular edema after successful treatment [13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…26. Consider vitrectomy in eyes with chronic or diffuse DME that is non-responsive to laser treatment (Level III-1 evidence) [45][46][47][48] , or if related to vitreomacular traction (Level III-1 evidence). 27.…”
Section: Role Of Vitrectomy In Managing Diabetic Retinopathymentioning
confidence: 99%
“…However, to date, the few RCT of vitrectomy for DME (Table 3.2.1) have relatively small sample size and short follow-up, with inconsistent results [45][46][47][48] .…”
mentioning
confidence: 99%
“…15,19,37,41,50,51 Our trial included 40 patients 19 with an attached but otherwise normal posterior hyaloid (ie, no clinical traction or PVD), who were randomised to either more laser or vitrectomy with ILM peeling. We found no clinically or statistically significant difference in acuity or macular thickness reduction between the lasered control and vitrectomy groups at 12 months follow-up.…”
Section: Introductionmentioning
confidence: 99%